Knowledge Socialization and COVID-19 Prevention Among Senior Secondary School Students in Mesuji Regency - Vikto Agus Wibowo; Happy Komikesari (Jurnal Studi Multidisiplin Ilmu, 2025)
Purpose: This study examines the design, implementation, and outcomes of a COVID-19 knowledge socialization program conducted by a university community service team at a senior secondary school in a green-zone area, focusing on its impact on student health protocol adherence and awareness of traditional herbal immune-support practices. Methodology: A qualitative service-learning evaluation design was applied. A single two-hour socialization session was delivered to thirty students at SMAN 2 Way Serdang, Mesuji Regency, on 23 July 2020, covering viral biology, external prevention measures, and empon-empon herbal immune support. A structured Google Form questionnaire capturing pre- and postsession health protocol compliance was completed by fifteen respondents. Results: Before the intervention, 80% reported compliance and 20% occasional adherence. After the session, 33% increased compliance, 47% remained unchanged, one became consistent, and two improved slightly. Conclusions: A single in-person socialization session combining biomedical and herbal health education can improve health protocol adherence and knowledge among adolescents in green-zone schools. Limitations: The study is limited by a small self-selected sample, one session, self-reported data, and no control group, limiting generalizability and causal inference. Contributions: This study presents a low-resource, replicable model for adolescent pandemic risk communication integrating biomedical and traditional health knowledge.